Public Services Coproduction: A conceptual review based on the relationship between the Citizen and the State - Sarantidis, George (Social Cohesion and Development, 2023)
Public service coproduction is the term used to indicate the active involvement of the citizen/service-user in the process of design and production of that service. The evolu-tion of the concept of Citizenship into that of Active Citizenship and the role attribut-ed to the Citizen-Coproducer, has led scientists to support the idea of a quasi-renegotiation of the traditional Social Contract into a new context based on principles of the coproduction paradigm. The article argues that Coproduction is no panacea: participation in itself can become the antidote neither to the social inequalities nor the absence of balance between the various social groups